Differences in TGF-β1 signaling and clinicopathologic characteristics of histologic subtypes of gastric cancer. Issue 1 (December 2016) - Pak, Kyung; Kim, Dong; Kim, Hyunki; Lee, Do; Cheong, Jae-Ho
Abstract Background Aberrant TGF-β1 signaling is suggested to be involved in gastric carcinogenesis. However, the role of TGF-β1 in intestinal-type [i-GC] and diffuse-type [d-GC] gastric cancer remains largely unknown. In this study, we evaluated the expression of TGF-β1 signaling molecules and compared the clinicopathological features of i-GC and d-GC. Methods Patients (n=365, consecutive) who underwent curative gastrectomy for gastric adenocarcinoma in 2005 were enrolled. We performed immunohistochemical staining of TGF-β1, TGF-β1 receptor-2 (TβR2), Smad4, p-ERK1/2, TGF-activated kinase (TAK)1, and p-Akt in 68 paraffin-embedded tumor blocks (33 i-GC and 35 d-GC), scored the expression according to the extent of staining, and evaluated differences between the histologic subtypes. Results Patients with d-GC differed from those with i-GC as follows: younger and more likely to be female; more aggressive stage; higher recurrence rate. The expression of TGF-β1 and TβR2 was higher in i-GC (P = 0.05 andP <0.001, respectively). The expression of Smad4, a representative molecule of the Smad-dependent pathway, was decreased in both subtypes. TAK1 and p-Akt, two major molecules involved in the Smad-independent pathway, were over-expressed (69 87 % of cases stained), without a statistically significant difference between i-GC and d-GC. Of note, the expression of p-ERK1/2, a Smad-independent pathway, was significantly increased in i-GC (P = 0.008). Conclusions The clinicopathological characteristics vary in different histologic gastric cancer subtypes. Although TGF-β1 signaling in gastric cancer cells appears hyper-activated in i-GC compared to d-GC, the Smad-dependent pathway seems down-regulated while the Smad-independent pathway seems up-regulated in both histologic subtypes.